Some Remarkable Evidence of Pierre de Fermat Last Theorem - BHAT, KHURSHID AHMAD (European Journal of Applied Sciences, 2022)
During the mid seventeenth century many legendry researchers contributed a lot in the fields of mathematical sciences, Pierre de Fermat was one of them who has contributed some excellent results in mathematics, one of his famous work, a theorem called last theorem of Fermat in which he said, “It is impossible … for any number which is a power greater than the second to be written as the sum of two like powers Xn + Yn = Zn for n > 2. I have as truly marvellous demonstration of this proposition which this margin is too narrow to contain.” Andrew Wiles et. al. provide a solution that shows that the equation does not holds for values n > 2. Pierre de Fermat was talking about the marvellous demonstration of his theorem, so the challenge is still open. In this paper some interesting results are highlighted, may be it helps the researchers to achieve the legitimacy what Fermat was talking about.